Pengaruh Kecerdasan Emosi dan Kecerdasan Spiritual Terhadap Perilaku Organisasi Sekolah di Pondok Pesantren Muhammadiyah Boarding School Yogyakarta - Ezra Najwa Wahyu; Novia Fetri Aliza (Islamic Counseling: Jurnal Bimbingan dan Konseling Islam, 2023)
The purpose of the study is to figure out whether there is a role between emotional and spiritual intelligence on organizational behavior. Islamic boarding schools are religious institutions that provide education and teaching as well as develop and disseminate Islam. An organization in the boarding school is the spearhead for running all activities at the boarding school since they are the leaders who drive all policies and work programs to nurture the character of other students. Emotional intelligence or also known as “EQ” is a subset of social intelligence that involves monitoring social emotions involving the abilities of others. Meanwhile, spiritual intelligence is the one to face and solve problems of meaning and value, namely intelligence to set behavior and life in a broader and richer context, and intelligence to assess that one’s action or way of life is more meaningful than others. The method in this study was quantitative and the data collection technique was through a questionnaire. Then, the data were analyzed using multiple linear regression analysis. The role of emotional and spiritual intelligence in school organizational behavior at Muhammadiyah Boarding School, Yogyakarta, is equal to 72.4%.